A fun and effective self-learning approach to teaching microcontrollers and mobile robotics. Issue 4 (October 2015) - Cubero, Samuel N
This paper describes how students can be guided to become their own best teachers, able to test their newly acquired skills with only minimum or no direct assistance from an instructor or lecturer. 'Closed-loop' student-centred learning and problem-based learning approaches are described, involving weekly lectures and hands-on lab activities that keep students highly curious, motivated and engaged in self-regulated learning. Students are required to design and test their own original circuits and software code by modifying, extending or expanding the sample circuits and example code described in the lecture notes, in order to complete and demonstrate specific objectives or requirements for each weekly lab session. These 'closed-loop' student-centred learning labs ensure that all teams of students achieve a common or minimum acceptable level of practical skills, which adequately prepares them for a 'design-and-build' competition. This style of learning also helps develop generic life-long learning skills such as investigating and identifying problems (problem definition and analysis), independent research and experimentation, decision making, communication and teamwork. Even without any prior hands-on experience with electronic circuit design, programming and microcontrollers, each team of students was able to apply and demonstrate new knowledge and skills, devise and test original designs for circuits and software without any supervision, solve and fix complex problems successfully and confidently, and build an operational remote-controlled electric vehicle or mobile robot for a final competition. Some went even further and built sensor-guided fully autonomous mobile robots. Three different competitions described in this paper include a timed racing car competition, a multi-player box grabbing contest over a rocky obstacle course and a 'robot wars' competition that was televised on Channel 10 news in Australia.